Numbers of Eurasian beaver (Castor fiber) in the Czech Republic, causes of their admission to rehabilitation centres and release rates in the period from 2010 to 2020 - Gabriela Kadlecová; Filip Kounek; Eva Voslářová; Vladimír Večerek (PLoS ONE, 2025)
The Eurasian beaver (Castor fiber) is the largest European rodent. This endangered species is an ecosystem engineer capable of providing several positive impacts in the ecosystems. However, it is also a cause of frequent conflicts with humans. In 2020, the beaver population in the Czech Republic reached 14,610 individuals, with the highest numbers in the Pilsen, Olomouc and Southern Moravian regions. Concurrently, beavers were most often admitted to rehabilitation centres in these regions, and their total numbers in rehabilitation centres increased in the period from 2010 to 2020 (p < 0.01). Beavers were most often admitted after falls into pits and other openings (29.76% of admitted animals) and after a collision with a vehicle (11.9%). Almost half (47.62%) of admitted beavers were released to the wild after their recovery. The mortality rates differed for different causes of admission, with the highest mortality in beavers admitted after a collision with a vehicle (70%) and beavers with bite wounds (67%). There was no significant difference (p > 0.01) in the length of stay in the centres of the beavers that were released to the wild after being treated for the monitored causes of admission. In view of these results, it is important to place particular emphasis on preventive interventions in nature reducing anthropogenic risks for Eurasian beavers and educating the public about the beneficial activities of this endangered species.